2012
DOI: 10.2478/v10019-012-0010-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the tumourigenic and metastatic properties of SK-MEL28 melanoma cells surviving electrochemotherapy with bleomycin

Abstract: BackgroundElectrochemotherapy is a local treatment combining chemotherapy and electroporation and is highly effective treatment approach for subcutaneous tumours of various histologies. Contrary to surgery and radiation, the effect of electrochemotherapy on metastatic potential of tumour cells has not been extensively studied. The aim of the study was to evaluate the effect of electrochemotherapy with bleomycin on the metastatic potential of human melanoma cells in vitro.Materials and methodsViable cells 48 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
5
1
Order By: Relevance
“…In previous studies, the intrinsic susceptibility of the cells to bleomycin was an important predictive factor for the antitumour effectiveness. Several studies have demonstrated the differences in cell sensitivity to electrochemotherapy . However, the results of the present study demonstrated that other factors, related to the tumour micro‐environment, also influence the tumour response to electrochemotherapy.…”
Section: Discussioncontrasting
confidence: 45%
“…In previous studies, the intrinsic susceptibility of the cells to bleomycin was an important predictive factor for the antitumour effectiveness. Several studies have demonstrated the differences in cell sensitivity to electrochemotherapy . However, the results of the present study demonstrated that other factors, related to the tumour micro‐environment, also influence the tumour response to electrochemotherapy.…”
Section: Discussioncontrasting
confidence: 45%
“…The knowledge of the cell death mechanisms and tumorigenic properties of the cells, and development of advanced therapies is therefore a key to successful treatment 18,19…”
Section: Discussionmentioning
confidence: 99%
“…Trypsinized B16.F10 mouse melanoma cells were suspended in electroporation buffer and pDNA added as described previously. 62 Aliquots were transferred to cuvettes or pipetted between 2 mm gap steel electrodes. Two different pulse types were used, eight square wave electric pulses at an amplitude over distance ratio 600 V/cm, a pulse duration of 5 ms, and a frequency 1 Hz (EP), and six square wave electric pulses at an amplitude over distance ratio 1,300 V/cm, a pulse duration of 100 µs, and a frequency of 4 Hz (EP1) electric pulses were generated by an in-house built electroporator (GT-01, Faculty of Electrical Engineering, University of Ljubljana, Slovenia) or with a T820 Electrosquare porator (BTX Molecular Delivery Systems, Holliston, MA).…”
Section: Methodsmentioning
confidence: 99%